The Methylenetetrahydrofolate Reductase TT677 Genotype Is Associated with Venous Thrombosis Independently of the Coexistence of the FV Leiden and the Prothrombin - Margaglione, Maurizio; D’Andrea, Giovanna; d’Addedda, Marina; Giuliani, Nicola; Cappucci, Giuseppe; Iannaccone, Luigi; Vecchione, Gennaro; Grandone, Elvira; Brancaccio, Vincenzo; Minno, Giovanni Di (Thrombosis and Haemostasis, 1998)
A polymorphism, C→T677, in the methylenetetrahydrofolate reductase (MTHFR) gene has been identified as a cause of mild hyperhomocysteinemia, a risk factor for venous thrombosis. We have investigated the frequency of the TT genotype in 277 consecutive patients with confirmed deep venous thrombosis and 431 healthy subjects. The TT MTHFR genotype was more frequent in patients than in controls (25.6% vs. 18.1%; p = 0.016). The risk of thrombosis among carriers of this genotype was significantly increased [odds ratio: 1.6 (95% CI: 1.1-2.3)]. The estimated risk associated with the TT genotype was 2.0 (95% CI: 1.3-3.1) in subjects with (n = 122), and 1.3 (95% CI: 0.8-2.0) in those without (n = 155) predisposing (hereditary, acquired or circumstantial) risk factors for venous thrombosis. Factor V Leiden and prothrombin G→A20210 are known risk factors for venous thrombosis. After stratification for FV Leiden and prothrombin A20210 mutations, a significant association was also observed. After adjustment for sex, FV Leiden and prothrombin A20210 mutation, the estimated risk of venous thrombosis among carriers of the TT MTHFR genotype was 1.7 (95% CI: 1.2-2.6). The TT MTHFR genotype is independently associated with venous thrombosis, mainly among individuals with a high risk profile.